Benefits of BBIN Motor Vehicle Agreement to the Northeast region: A supply chain analysis - Nisha Taneja (Indian Council for Research on International Economic Relations (ICRIER), 2024)
This paper examines how the BBIN MVA can help in improving the export competitiveness of the North eastern region. Using secondary data and an in-depth primary survey a detailed examination of supply chain of two key items - pharmaceuticals and fresh and processed pineapple is undertaken to understand the impediments in the inbound and outbound supply chains. The efficiency of current supply chains is measured in terms of time and cost incurred in various stages of the supply chains and indicative costs on alternative routes are obtained to assess how the sectors could benefit and improve their export competitiveness. The paper suggests measures the NER states and the Centre can adopt to improve the export competitiveness of the region. Some of the suggestions are related to improving recording of export data, improving functionality of inland container depots in the Northeast, improving the logistic ecosystem, creating backward linkages, addressing trade policy distortions and adopting capacity building measures to improve the quality of the workforce in the logistic sector.
Keywords: F02; F13; L5; 330; BBIN MVA; Northeast Region (NER); exports; supply chain; pharmaceuticals; pineapple